Stiffness‐ and wettability‐dependent myoblast cell compatibility of transparent poly(vinyl alcohol) hydrogels1. Issue 2 (16th November 2012) - Gupta, Siddhi; T, Greeshma; Basu, Bikramjit; Goswami, Sudipta; Sinha, Arvind
Abstract: This study reports the in vitro compatibility of muscle cells (C2C12 mouse myoblast cell line) with the transparent poly(vinyl alcohol) (PVA) hydrogels and the results are explained on the basis of surface wettability, crystallinity, and nanoscale elastic stiffness property. Nanoindentation was carried out with a maximum load of 100 μN for all the hydrogel compositions and the properties such as elastic stiffness, hardness and total work done during indentation were computed. The difference in cell viability as well as adhesion of cultured myoblast cells on the investigated hydrogel substrates were discussed in reference to the difference in the nanoscale elastic properties, crystallinity, and surface wettability. An important result has been that both elastic stiffness and surface wettability synergistically influence myoblast viability/adhesion on PVA hydrogels. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.